The role of sacrificial target material in micromachining of glass using laser-induced plasma-assisted ablation (LIPAA). Issue 7 (26th July 2021) - Rahman, T.U.; Qayyum, H.; Amin, U.; Ullah, S.; Rehman, Z.U.; Dogar, A.H.; Rafique, M.; Qayyum, A.
Abstract : Laser produced metal plasma was used to fabricate micro-craters on the surface of the soda lime glass. The glass micro-crater machined by a single laser pulse is the first step towards the fabrication of a complex optical component and an elongated channel for the microfluidic devices. In this study, the role of the type of sacrificial material plasma on the structure of glass micro-craters was explored. For this purpose, aluminum and tungsten were used as the sacrificial target materials. The laser fluence and the gap distance between glass and metal target were varied in the range of 27–970 J/cm 2 and 0–500 μm, respectively. The optical microscope and surface profilometer were used to analyze the structure of micro-craters. The size of glass micro-crater was observed to depend on the laser fluence for both Al and W plasmas. However, the size of glass micro-crater fabricated by Al plasma was much bigger than that of the W plasma. Moreover, the structure of the micro-crater also depends on the gap distance. The measured ablation yield of the metal targets, size of the expanding plasma and physical processes occurring at the plasma–glass interface were used to explain the observed difference in the structure of glass micro-craters fabricated by Al and W plasmas.